Sentiment Analysis On Boycott Movement: NVivo Approach - Azzahro, Siti Fatimah; Indra, Indra (LPPM ISNJ Bengkalis, 2024)
Many countries have carried out the boycott, divestment, and sanction (BDS) movement. Research on this topic contains an interesting sentimental side and needs to be mapped to help future research. This study aims to determine the problem's evolution and mapping, along with sentiment analysis related to BDS. This study uses a descriptive statistical analysis approach combined with meta-analysis and sentiment analysis of secondary data in the form of metadata from 81 Scopus-indexed articles published over the past 15 years, which were then processed using NVivo 15. The findings of this study reveal that the majority of studies have a somewhat negative perspective on BDS. Negative sentiment shows that many studies use sharp and negative sentences, as well as sentences that cause debate; this is related to the